Advanced critical temperature method for steel beams exposed to different fire scenarios. (October 2022) - Song, Tian-Yi; Qu, Xing-Yu; Zhou, Hongyuan; Xiang, Kai
Abstract: The early-warning of fire-induced failure of structural members is becoming more and more attractive to the fire department since it can provide warning signal to the firefighters at the scene of a building fire. Temperature is a type of easily-measured parameter in fire condition, and can reflect the ultimate state of structural members to some extent, therefore it has the application potential to indicate the failure of structural members in fire. The traditional critical temperature method (CTM) in Eurocode 3 or Chinese standard GB 51249–2017 has been widely used in the fire safety design of steel members, but it cannot be extended to the early-warning of fire-induced failure directly. Based on the traditional CTM, this paper presents an advanced critical temperature method for simply-supported H-shaped steel beams under different fire scenarios. Finite element analysis (FEA) models were established and validated to investigate the critical temperatures of H-shaped steel beams. Based on the numerical analysis, guidelines for confirming the positions of characteristic temperature points (CTPs) and values of refined critical temperatures (RCTs) on H-shaped steel beams were proposed, and parametric analysis results indicated that the longitudinal fire scenario, perimeter of beam section and beam load ratio were the key influencing parameters. Finally, a design table was proposed to determine the positions of CTPs and values of RCTs of simply-supported H-shaped steel beams with 2-hour fire rating time, which can be used in the early-warning of fire-induced failure directly.